Pengaruh Penggunaan Media Lapbook terhadap Kemampuan Berpikir Simbolik Anak Usia 5-6 Tahun - Tulhidaya, Siska; Herman, Herman; Hajerah, Hajerah (UIR PRESS, 2026)
Children’s symbolic thinking ability, particularly at the age of 5–6 years, is often hindered by difficulties in recognizing number and letter symbols, which is partly caused by the limited use of media in the learning process. In fact, the use of media in learning plays a crucial role in enhancing children’s abilities. One of the instructional tools that can be employed is the lapbook, which serves as a learning medium to stimulate children’s symbolic thinking skills. This study aims to determine the Effect of Using Lapbook Media on the Symbolic Thinking Skills of Children Aged 5-6 Years at Al-Furqan Minasaupa Islamic Kindergarten. The research approach used is a quantitative approach with a Pre-Experimental research type in the form of One Group Pretest-Posttest. The population in this study were class B students aged 5-6 years at Al-Furqan Minasaupa Islamic Kindergarten. The population in this study were all class B students with a total of 47 children. The sample in this study was 16 children in class B2. The sample selection was carried out using a purposive sampling technique. Data collection techniques used in this study were observation, testing, and documentation. The data analysis technique used is descriptive statistical analysis and non-parametric analysis, namely the Wilcoxon Signed-Rank Test using the SPSS 25 application. The results of the data analysis of class B2 students before being given treatment using lapbook media were 14.50 and after being given treatment using lapbook media, an increase of 22.81 was obtained. The test results show that sig. (2-tailed) 0.000 ˂ 0.05 then H1 is accepted, H0 is rejected. So it can be concluded that the use of lapbook media has an effect on the symbolic thinking ability of children aged 5-6 years at Al-Furqan Minasaupa Islamic Kindergarten.